Designing and validating the study on the influence of social media influencers scale - Wu, Jiayu; Mohd Mothar, Noor Mayudia; Ali, Anuar (Universiti Teknologi MARA, Kedah, 2025)
As the influence of influencers continues to expand, influencer marketing has become one of the mainstream sales methods in China. As a communication bridge between influencers and consumers, social media promotes the development of e-commerce and shortens the distance between audiences and influencers. With the rapid growth of social media in recent years, more and more women are willing to achieve self-transformation by dressing up and making up. They confidently share their cosmetics and dressing-up experiences on social media platforms. Therefore, this preliminary study aims to explore the influence of social media influencers on the cosmetics purchasing decisions of young female consumers in China. This study uses the questionnaire survey method in quantitative research and selects four universities in Shaanxi Province of China through probability sampling. Through the normal distribution analysis and reliability and validity analysis of 292 samples of young female consumers in China, the researchers concluded that the questionnaire has a high reliability and validity. Therefore, the questionnaire can be used to explore the relationship between influencers and consumers' purchasing decisions.